Cultural Ecosystem Services Provided by Coralligenous Assemblages and Posidonia oceanica in the Italian Seas - Zunino, Serena; Melaku Canu, Donata; Marangon, Francesco; Troiano, Stefania (Frontiers in Marine Science, 2020)
Posidonia oceanica meadows and coralligenous reefs are two Mediterranean ecosystems that are recognised as suppliers of valuable ecosystem services (ESs), including cultural services. However, valuation studies on these ecosystems are rarely addressed, and mainly focusing on provisioning and regulating services. Here we focus on the cultural services provided by P. oceanica and coralligenous, by addressing a specific group of users. Through an online survey submitted to Italian scuba divers, we assess their willingness to pay for a dive in the two ecosystems and how their preferences will change under different scenarios of degradation. Diving preferences are assessed using a discrete choice experiment. The results confirmed that ecological knowledge is associated with higher ecosystem values. Moreover, results confirm and assess how a high degradation of coralligenous and P. oceanica habitats would reduce the value of the underwater environment, by decreasing scuba diver satisfaction and their return visit rate. Considering a 50% reduction in the coverage of keystone species, the marginal willingness to pay decreased by approximately €56 and €18, respectively, for coralligenous reefs and P. oceanica, while the willingness to pay decreased by approximately €108 and €34, respectively, for a total reduction in coverage. Our results can be used to support the marine ecosystem-based management, and the non-destructive use of the Mediterranean Posidonia oceanica meadows and coralligenous reefs.